The earliest translations of Emily Dickinson's poetry in Slovene - Petrič, Jerneja (Acta neophilologica, 2006)
The article addresses the issue of the earliest translations of Dickinson's poetry in Slovene. Only 6 of the total number of 19 poems, translated into Slovene by Vatro Grill, were published in his 1979 memoir Med dvema svetovoma (Between Two Worlds). The other 13 poems included in Grill's manuscripts were never published. In the first part of her article, the author briefly surveys the translations of Dickinson's poetry into Slovene by Mart Ogen, Aleš Debeljak, Ivo Svetina and Miklavž Komelj. In the second part, the focus is on Grill's translation of two poems by Emily Dickinson whereby the translator's ability to capture the meaning of Dickinson's verse is measured against Mart Ogen's translation of the same poems.
Keywords: American literature; ameriška književnost; ameriška poezija; Dickinson, Emily, 1830-1886; Literarne študije; prevajanje; prevodi; translation